Simulation on tsunami-like solitary wave run-up around a conical island using a modified mass source method. Issue 1 (1st January 2019) - Ma, Zhe; Zhou, Ting; Sun, Jiawen; Zhai, Gangjun
Abstract: Predicting the maximum run-up height and inundated area caused by tsunami events has been a hotly debated topic recently. Nevertheless, the wave height-to-depth ratios (nonlinearity) adapted previously tended to be conservative, considering the fact that a tsunami wave is an extreme wave condition with large wave height. In the present study, a mass source wave-generating approach for highly nonlinear waves is presented using our in-house solver, DUT-FOAM, which is a hydrodynamic solver developed using the open source code library OpenFOAM. By fully considering the mass output from the source region, a more reasonable mass source function has been obtained to compensate for the inadequacy of original method in simulating highly nonlinear waves. A newly designed numerical wave tank is performed for different nonlinearities. Numerical simulations of tsunami wave propagating to a conical island are carried. Fairly good agreements are obtained from the qualitative and quantitative comparisons between numerical results (Liu, Cho, Briggs, Kanoglu, & Synolakis, 1995) and laboratory data (Briggs, Synolakis, Harkins, & Green, 1995) regarding run-up maps around the island. The comparison reveals that present model offers a fast and accurate way to simulate highly nonlinear waves and is potentially useful and efficient for forecasting the run-up heights.